A fast converging algorithm for Landau's output error method - Harteneck, Moritz; Stewart, Robert W. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper an approach to on-line ARMA parameter estimation based on a pseudo-linear regression and a QR matrix decomposition is developed. The algorithm has proven to be stable and has fast convergence properties if the unknown ARMA model satisfies the strictly positive real condition.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka